Ex Post Assessments of Members with a Longer-Term Program Engagement-Revised Guidance Note. (Policy Papers; Policy Paper ;, 2010)
Financial sector issues and policies are central to the Fund's surveillance mission, as the recent crisis has amply demonstrated, and the institution has placed a high priority on enhancing the coverage and depth of analysis of financial sector issues in surveillance. Achieving this goal requires far-reaching operational and resource adjustments, which are already underway. However, these alone may not be enough. Changes in the Fund's mandate and modalities of surveillance may also be needed. A key goal of these changes should be to strengthen multilateral surveillance. New analytical tools and effective forms of engagement at the global level are crucial for financial surveillance, given an increasingly interconnected and globalized international financial system. At the same time, financial surveillance at the country level should also be strengthened and become a central part of the Article IV consultation process.